KAJIAN STILISTIKA NOVEL PADUSI KARYA KA’BATI - Daratullaila Nasri (tuahtalino, 2019)
This research has purpose to reveal the characteristic of author’s figure of speech in Padusi novel by Ka’bati. The object of this research is to discover whether the figure of speech which used by the author shows his ideas and thought regarding the live of Indonesian labor in foreign country. Therefore, the approach used is stylistic. Stylistic, in this matter, merely sees the linguistic aspect and does not graze the content. The linguistic aspect is exposed using a concept set by Gorys Keraf. Method used in the research is qualitative. Out of this research can be concluded that there are several figure of speech used by the author. Those figures of speech are based on the structure of the sentences and either the sentences are direct or not. Figures of speech based on the structure of sentences are majority found as climax figure of speech. Based on the meaning directness, it divided into two, which is rhetorical and allegory. In rhetorical, the one most found is euphemism, paradox and tautology. In allegory, the ones found the most are metaphor, simile, and irony. Each figure of speech has its own different function. Those function exposed the portrait of Indonesian labor abroad.